Impact of globalization, tourism, energy, and education on load capacity factors in selected 14 Indo-Pacific nations: an advanced econometric analysis - Quamrul Alam; Liton Chandra Voumik; Md. Hasanur Rahman; Md. A. K. Azad Khan (All Earth)
The purpose of this study is to investigate the impact of globalisation, tourism, renewable energy, education, population, and GDP on load capacity factors (LCF) in 14 selected Indo-Pacific nations. The research employed data from 1991 to 2022 to estimate the long-term relationships. The research considered Generalized Least Squares (GLS) and Quantile Regression as the baseline models. To check the robustness, the research applied fully modified ordinary least squares, dynamic ordinary least squares, and canonical cointegrating regression. The findings show that GDP, renewable energy, tourism, and education improve LCF significantly in the Indo-Pacific region. Conversely, population and globalisation significantly deteriorate LCF. The GLS method states that the GDP and tourism coefficients are 0.074 and 0.043, meaning a 1% increase in GDPPC and tourism raises LCF by 0.074% and 0.043%, respectively. Similarly, a 1% increase in renewable energy and education increases LCF by 0.223% and 0.414%, respectively. Contrarily, the coefficients of population and globalisation show a 1% increase in population and globalisation reduces LCF by 0.062% and 0.1111%. The robustness checks fully validate the baseline regression results. This study contributes to the body of the literature by emphasising the multifaceted effects of socioeconomic, demographic, and environmental factors on LCF in the Indo-Pacific region.